Perencanaan Pengadaan Bahan Baku Karoseri Menggunakan Metode Material Requirements Planning - Fitriana Fitriana; Winarno Winarno (Universitas Indraprasta PGRI Jakarta, 2023)
One part of the company's operational process is a production process, which is is the core activity of a manufacturing company. In the production process, a company takes a resource in the form of raw materials to be processed into products. The problems that often occur are a shortage and excess of raw material inventory. The company is required to be able to solve these problems so that the production process runs effectively and efficiently. Therefore, it is necessary for the company to have a method of planning and controlling raw material inventory to determine the right time for ordering and minimizing inventory costs. The method used is the forecasting method with linear regression analysis and material requirements planning with lot-sizing techniques: lot for lot, economic order quantity, and period order quantity. The results show that the average product demand forecast per month is 85 units. Then, the lot-sizing techniques that produce the lowest cost are the lot for lot technique and the period order quantity with a total cost of Rp. 11,524,753.